PERBEDAAN STATUS GIZI ANTARA BAYI YANG DIBERI ASI DENGAN BAYI YANG DIBERI PASI PADA BAYI KURANG DARI 6 BULAN DI DESA KATEGUHAN KECAMATAN SAWIT - Rahayu Setyaningsih; Tri Susilowati (KOSALA : Jurnal Ilmu Kesehatan, 2013)
Background. Mother's Milk is the first natural food for infants and should begiven without any extra food to infants in 6 months. But today there are manyparents who provide complementary feeding earlier less than 6 months. Both ofthese circumstances affect the nutritional status of infants.The purpose of the study was to determine differences in the nutritional statusof infants breast-fed infants fed with infants complementary feeding in the villageKateguhan Sawit subdistrict.Methods comparative descriptive research design using cross sectionalapproach, the population consists of infants aged less than 6 months the totalnumber were 39 infants, the sampling technique is total sampling, tdataanalyzed using Mann Whitney U Test.The conclusion the results of the nutritional status of infants exclusivelybreastfed most normal nutritional status of as many as 14 infants (93.3%) whilethe infants with complementary feeding largely nourished baby fat as many as15 infants (62.5%). There are significant differences between the nutritionalstatus of infants fed breast milk and complementary feeding (p value 0,000<0,05)Keywords : mother’s milk, complementary feeding, nutritional status